Formação de professores para promoção da inclusão escolar de alunos surdos no contexto da educação profissional e tecnológica de nível médio - Menezes, Melissa Rossana de Oliveira (2020)
The mandatory vacancies reservation for People with Disabilities (PcD) in Brazilian’s Federal Education Institutions has been a challenge to carry out an effective school inclusion process. As a result, this work originated from a concern about the deaf student’s school inclusion process in the Professional and Technological Education at the Federal Institute of Alagoas, which led to the development of a diagnostic research focused on the need for Educational Product’s elaboration aimed at training teachers who work in these contexts of EPT. The methodological path used for the diagnostic research elaboration was based on the qualitative approach, whose method is that of action-research, through a questionnaire applied to the teachers of an Integrated Middle Level Course of one of the Campuses of the Institute. The data collected presented the following gaps in this course inclusion’s process: i) lack of acceptance in the admission of the deaf student, therefore the missing of pedagogical planning adapted to the Deaf Culture, ii) necessity to hire more Libras’s translators and interpreters for monitoring and supporting curricular activities and, iii) teachers continued training’s absence on school inclusion. These data, analyzed in dialogue with the authors used in the theoretical foundation, served as a basis for the Educational Product’s elaboration for those teachers, which aimed to an inclusive teaching process improvement of the teaching and learning process of deaf students. The results obtained from the research undertaken highlighted the importance of carrying out initiatives such as teacher training aimed at school inclusion, as well as the relevance of Deaf Culture knowledge for the teaching of deaf students, and, finally, the need for continuing education for teachers, so that teaching practice is in fact revised from the principles that integrate Inclusive Education.